The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1365-2125.2003.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampicin on the pharmacokinetics and pharmacodynamics of nateglinide in healthy subjects

Abstract: Aims Our aim was to investigate the effects of rifampicin on the pharmacokinetics and pharmacodynamics of nateglinide, a novel short-acting antidiabetic drug. Methods In a randomized crossover study with two phases, 10 healthy volunteers took 600 mg rifampicin or placebo orally once daily for 5 days. On day 6 of both phases, they ingested a single 60 mg dose of nateglinide. Plasma nateglinide and blood glucose concentrations were measured for up to 7 h postdose. Results Rifampicin decreased the mean AUC(0,7 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…It has been shown that the magnitude of other pharmacokinetic interactions involving nateglinide are generally smaller than those affecting other antidiabetic drugs. For example, rifampicin at 600 mg daily for 5 days decreased the AUC(0, •) of nateglinide by only 22% [54], whereas the same treatment caused a 57% decrease in the AUC(0, •) of repaglinide [55]. Similarly, fluconazole given at 200 mg (first dose 400 mg) daily for 4 days increased the AUC(0, •) of nateglinide by 48% [21] and that of glimepiride by 138% [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the magnitude of other pharmacokinetic interactions involving nateglinide are generally smaller than those affecting other antidiabetic drugs. For example, rifampicin at 600 mg daily for 5 days decreased the AUC(0, •) of nateglinide by only 22% [54], whereas the same treatment caused a 57% decrease in the AUC(0, •) of repaglinide [55]. Similarly, fluconazole given at 200 mg (first dose 400 mg) daily for 4 days increased the AUC(0, •) of nateglinide by 48% [21] and that of glimepiride by 138% [16].…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone is metabolised largely by CYP2C8, and rifampicin decreases concentrations of rosiglitazone by 54–65% and of the related drug pioglitazone by 54% 9597. Nateglinide, a short-acting insulin secretagogue given to prevent postprandial hyperglycaemia, is metabolised by oxidative bio transformation, with involvement from CYP2C9 and CYP3A4; its area under the curve is reduced by only 24% with no appreciable glycaemic effect when given with rifampicin 98. Repaglinide, another related drug, had an area under the curve that was decreased by 31–57% when given with rifampicin, although its glucose-lowering effect was reduced in one study and unchanged in another 99,100.…”
Section: Pharmacological Issues In the Co-management Of Diabetes Mellmentioning
confidence: 99%
“…Rifampicin is a very potent inducer of these enzymes (Venkatesan 1992, Burman et al. 2001; Niemi et al. 2003a).…”
Section: Combined Treatment Of Dm and Tbmentioning
confidence: 99%